LITOFASIES ANALYSIS IN THE CIPAMINGKIS RIVER ROCK FORMATION JATILUHUR, BOGOR, WEST JAVA. - Gani, Reza Mohammad Ganjar; Firmansyah, Yusi; Nurdrajat, Nurdrajat; Fathin, Muhammad Kayis (Journal of Geological Sciences and Applied Geology, 2021)
The Sedimentary rocks result from the breakdown of previously transported rocks deposited and lithified. Sedimentary rocks cover almost 80% of the earth's crust (Folk, 1974). The research was conducted in the Cipamingkis River, Jonggol District, Bogor Regency, West Java. The research area is included in the Cianjur Regional Geological Map Sheet (Sudjatmiko, 1972) and is included in the Dayeuhkaum Earth Map (1209 – 233) published by the Geospatial Information Agency (BIG). The Jonggol District, Bogor Regency, West Java, has a large river, the Cipamingkis R,iver, stretching from the northeast to the southwest of the study area. This river is included in the Jatiluhur Formation (Sudjatmiko, 1972). The facies is a rock body with a different combination of physical, chemical and biological characteristics from the surrounding rock body, which reflects its original conditions, namely the way it was transported and the way it was deposited. Two bodies of rock deposited simultaneously have different facies if they have differences in their physical, chemical and biological characteristics. Units and sediment structure components in the study area are grouped into six lithofacies: (1) Thin-Medium Sandstone Layer, (2) Massive Claystone, (3) Alternating Sandstone and Claystone, (4) Thick Sandstone Layer, (5) Alternating Fine Sandstone and Very Fine Sandstone, and (6) Slump Deposit. Description of facies by limiting physical and chemical characteristics is called lithofacies, and lithofacies is a facies analysis method by considering information about physical and chemical characteristics of rock layers (Nichols, 2009).